2015
DOI: 10.4314/ejhs.v25i1.3
|View full text |Cite
|
Sign up to set email alerts
|

The effects of a dentifrice containing propolis on <i>Mutans streptococci</i>: A clinico-microbiological study

Abstract: BACKGROUND: Propolis is a natural resinous mixture produced by honeybees, which exhibits antimicrobial, anti-inflammatory, cytostatic and cariostatic properties. The aim of the study was to evaluate the anti-bacterial efficacy of a propolis based dentifrice on Mutans Streptococci colonizing the oral cavity of young patients using Dentocult® SM strip mutans test. METHODS: Screening of 367 male subjects within the age group of 7-12 years was carried out. A total of 30 children were included in the study. They we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 22 publications
2
19
0
3
Order By: Relevance
“…8,9,26,27 Previous studies have reported the strong antimicrobial activity of propolis against several bacteria of the oral m icrobiome, i ncludi ng S. mutans. 1,2,28,29,30,31 As confirmed in our study, propolis and some of its isolated compounds, such as apigenin and tt-farnesol, 11 have been found to display a major effect on microbial virulence (e.g., polysaccharide production and acid tolerance), rather than affecting unspecific or specific microbiome viability, considered a highly desirable quality.…”
Section: Discussionsupporting
confidence: 71%
“…8,9,26,27 Previous studies have reported the strong antimicrobial activity of propolis against several bacteria of the oral m icrobiome, i ncludi ng S. mutans. 1,2,28,29,30,31 As confirmed in our study, propolis and some of its isolated compounds, such as apigenin and tt-farnesol, 11 have been found to display a major effect on microbial virulence (e.g., polysaccharide production and acid tolerance), rather than affecting unspecific or specific microbiome viability, considered a highly desirable quality.…”
Section: Discussionsupporting
confidence: 71%
“…The results of this study was supported by several studies (14,15) which studied antimicrobial effect of propolis on various oral microorganism and found that propolis had greater effect on oral bacteria and evaluated the antibacterial action of an extract of propolis on the concentration of Streptococcus mutans colonizing the oral cavity of young patients. They concluded that propolis extract possesses in vivo antimicrobial activity against S. mutans present in the oral cavity and might be used as an alternative measure to prevent dental caries This study also agreed with previous studies that (4,16) who concluded that propolis is very effective on oral pathogenic microorganisms (such as Streptococcus mutants, Candida albicans and Actinobacillus a. commitans) and concluded that propolis might be used as a natural mouthwash,an alternative to chemical mouthwashes, e.g., chlorhexidine.…”
Section: Discussionsupporting
confidence: 67%
“…Previous studies have proven that propolis could break down the bacterial cell wall and prevent bacterial cell adhesion. 12,22 Flavonoids and caffeic acid present in propolis are known to play an important role in reducing the inflammatory response by inhibiting the lipoxygenase pathway of arachidonic acid metabolism. Flavonoids and caffeic acid also aid the immune system by promoting phagocytic activities and stimulating cellular immunity.…”
Section: Discussionmentioning
confidence: 99%
“…The putative therapeutic properties of propolis could be related to its antibacterial, anti-inflammatory, antioxidative, and/ or tumoricidal activities. 5,6,7,8,9,10,11,12 Animal experiment results indicate that the alcoholic extraction of propolis induces the production of a tubular and better quality dentin than calcium hydroxide groups. 13,14 The present study was designed to compare the effect of propolis and MTA on the biological properties of human dental pulp cells (hDPCs), and lay the experimental foundation for propolis application in pulp therapy in the future.…”
Section: Introductionmentioning
confidence: 99%